2013
DOI: 10.1159/000346365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Late-Onset Neonatal Sepsis in Premature Infants Using Small Blood Volumes: Proof-of-Concept

Abstract: Background: Conventional blood culture is still the gold standard for sepsis diagnosis but results are not immediately available and pathogens are only detected in approximately 25% of cases. New molecular assays for the detection of blood stream pathogens are promising diagnostic tools. Objectives: The aim of the study was to adapt and evaluate a multiplex PCR system using 100 µl blood. -Methods: 46 blood specimens of very low birth weight infants (818 ± 242 g) with suspected sepsis were analyzed using the Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
(33 reference statements)
0
32
1
3
Order By: Relevance
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…45,69,[71][72][73][74][75][76][77][78][80][81][82][83][85][86][87][90][91][92][93][94][96][97][98][99][101][102][103]107,[109][110][111][112]114 Of these, nine studies reported blood volumes that did not comply with CE approval: Lehmann et al, 76 Lodes et al 92 and von Lilienfeld-Toal et al 71 all reported using 1 ml in adults; Bloos et al, 74 Lamoth et al, 75 Paolucci et al 99 and Sitnik et al 107 all reported using 3 ml in adults; Berger et al…”
Section: Details Of Index and Reference Tests Blood Sampling Methodsmentioning
confidence: 99%
“…community, emergency department, hospital, intensive/critical care, general/ specialist) was not reported for nine SeptiFast studies, 44,65,69,72,88,98,100,105,110 or for one multitest SeptiFast and SepsiTest study 118 (confidential information has been removed). The setting across the remaining studies varied (see Table 4).…”
Section: Study Design Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a small study on 34 infants with suspected cases of LOS [61], 7/7 etiologic agents of definitive neonatal sepsis were identified by the multiplex PCR, whereas only 3/7 were detected by culture. In a collective of 46 preterm infants with suspected neonatal sepsis [62], SeptiFast (Roche Diagnostics GmbH, Basel, Switzerland) multiplex real-time PCR was more sensitive than culture (90 % vs. 71 %), but less specific (80 % vs. 100 %) because of 5/21 non-infected patients with positive PCR for coagulase-negative staphylococci.…”
Section: Pcr On Whole Blood and Other Sterile Fluids Of Septic Neonatesmentioning
confidence: 99%